Inspirasi Batik Tamarind dari Cerita rakyat - Belinda Sukapura Dewi; ARLETI M. APIN; Ariesa Pandanwangi; Nuning Damayanti (LPPM Universitas PGRI Adi Buana Surabaya, 2021)
Batik is known not only for its beauty, but also for the values ​​it contains. This potential is very inspiring and gives an idea visualized into batik storytelling using the cold method of tamarin paste, a new approach that is more environmentally friendly. This technique has also been tested both domestically and abroad and has great potential for opportunities batik development with new ideas. An opportunity to preserve batik novelty that have no potential harass to traditional batik. This study applies the discussion of visual language to folklore theme batik works. In the earlier times, speech was common culture carried by elders to their children or grandchildren. Folktales in the form of legends, myths and fables are moral messages way conveyed in a friendly, fun but also educating with devotion. The theories and methods used to discuss two batik samples are taken from folklore which contains educational moral values. Based on a study of selected samples of batik works, it is known that the images or shapes on batik use the Space Time Flat (RWD) and Naturalist Perspective Moment Opname (NPM) systems simultaneously. Most of the depictions of motifs and shapes in batik still use the RWD system, although some forms also use NPM.